New naphthalene derivative from the leaves of Cassia grandis L. Issue 15 (3rd August 2017) - Trinh, Pham Thi Nhat; Luan, Ngoc Quoc; Tri, Mai Dinh; Khanh, Vu Duy; An, Nguyen Huu; Minh, Phan Nhat; An, Pham Ngoc; Thuy, Nguyen Thi Le; Phung, Nguyen Kim Phi; Dung, Le Tien
Abstract: Cassia grandis is used for the treatment of skin disorders, back pain, aches, etc. in Vietnamese traditional medicine. In this paper, phytochemicals of the leaves were investigated. A new naphthalene derivative (1, cassgranon D) and, seven known compounds rutin (2 ), afzelin (3 ), quercitrin (4 ), epicatechin (5 ), (-)-epiafzelechin (6 ), isoquercitrin (7 ) and aloe emodin (8 ) were isolated from the ethyl acetate and methanol extracts. Their structures were elucidated by spectral evidences (UV, IR, MS, 1 H, 13 C, DEPT, HSQC and HMBC NMR), as well as by comparing with published data. Abstract :